Enhancing ZIS Donor Loyalty Through The Role of Trust at Baitul Maal Hidayatullah East Kalimantan - Imam Salamun; Indra Indra (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study is motivated by the limited empirical research examining the direct effects of service quality, institutional image, communication, and donation convenience on donor trust and its subsequent impact on loyalty in zakat, infaq, and sadaqah (ZIS) donations. The objective of this research is to analyze the influence of service quality, institutional image, communication, and donation convenience on donor trust, as well as to examine the effect of donor trust on ZIS donation loyalty at Baitul Maal Hidayatullah East Kalimantan. This study employs a quantitative approach using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. Primary data were collected through closed-ended questionnaires using a 5-point Likert scale distributed to 240 active donors selected through purposive sampling. The findings reveal that service quality and institutional image have a positive and significant effect on donor trust, whereas communication and donation convenience show positive but statistically insignificant effects. Furthermore, donor trust significantly and positively influences ZIS donation loyalty. The study implies that improving service quality and strengthening institutional image are key strategies in building sustainable donor trust and loyalty.